2020
DOI: 10.1016/j.joca.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-related nociceptive behaviour following mechanical joint loading correlates with cartilage damage

Abstract: Objective: In osteoarthritis (OA), the pain-structure relationship remains complex and poorly understood. Here, we used the mechanical joint loading (MJL) model of OA to investigate both knee pathology and nociceptive behaviour.Design: MJL was used to induce OA in the right knees of 12-week-old male C57BL/6 mice (40 cycles, 9N, 3x/week for two weeks). Mechanical sensitivity thresholds and weight-bearing ratios were measured before loading and at weeks one, three and six post-loading. At these time points, sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 68 publications
(72 reference statements)
3
23
0
Order By: Relevance
“…Similarly, surgical destabilization models of PTOA consistently result in hindpaw allodynia when compared to sham operated animals; however, the onset, presentation, and duration of hindpaw allodynia is varied and different from that observed in this non-invasive PTOA model 29,32,33 . Recent work by Heegde and colleagues corroborates the findings of the current study and shows that mechanicallyinduced joint injury is associated with both acute onset and maintenance of hindpaw allodynia 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, surgical destabilization models of PTOA consistently result in hindpaw allodynia when compared to sham operated animals; however, the onset, presentation, and duration of hindpaw allodynia is varied and different from that observed in this non-invasive PTOA model 29,32,33 . Recent work by Heegde and colleagues corroborates the findings of the current study and shows that mechanicallyinduced joint injury is associated with both acute onset and maintenance of hindpaw allodynia 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar mechanical sensitization has been reported after repetitive cyclical subcritical loading in mice. 66 However, consistent with induction of PTOA, repetitive injury caused altered hindlimb weightbearing and reduced mobility; furthermore, pain-related behavior, particularly mechanical sensitization, was correlated with progression of tibiofemoral cartilage damage. 65,66 One hypothesized driver of this association is the accompanying neurovascularization of the osteochondral junction, a feature observed in osteoarthritic joints.…”
Section: Discussionmentioning
confidence: 87%
“…66 However, consistent with induction of PTOA, repetitive injury caused altered hindlimb weightbearing and reduced mobility; furthermore, pain-related behavior, particularly mechanical sensitization, was correlated with progression of tibiofemoral cartilage damage. 65,66 One hypothesized driver of this association is the accompanying neurovascularization of the osteochondral junction, a feature observed in osteoarthritic joints. 61 Osteoclast activity is one aspect of this process, with a recent mouse study demonstrating reduced joint innervation and pain responses when subchondral bone remodeling was inhibited.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Subchondral bone lesions will weaken its mechanical strength and the ability to buffer mechanical stress accordingly [29], which increases the risk of cartilage injury and accelerates the KOA process. Previous studies have found that the increased subchondral bone loss was positively correlated with the level of cartilage erosion in KOA [30,31].…”
mentioning
confidence: 81%